A Conceptual Map of Knowledge Transfer in Occupational Therapy Clinical Practice in Central South Africa - Azette Swanepoel; Corlia Janse van Vuuren; Shoba Nayar (Occupational Therapy International)
Conclusion: The conceptual map, a first of its kind in South Africa, presents empirical evidence of knowledge that is created and transferred in clinical practice in central South Africa. The conceptual map might provide a framework for collaboration amongst all stakeholders, such as patients, occupational therapists, and academics, to produce practice guidelines and occupational outcome measures to support evidence-based clinical practice.